Expert SQL Server 2008 Development - Aitchison, Alastair; Machanic, Adam (Apress : Imprint: Apress, 2009)
Expert SQL Server 2008 Development is aimed at SQL Server developers ready to move beyond Books Online. Author and experienced developer Alastair Aitchison shows you how to think about SQL Server development as if it were any other type of development. You'll learn to manage testing in SQL Server and to properly deal with errors and exceptions. The book also covers critical, database-centric topics such as managing concurrency and securing your data and code through proper privileges and authorization. Alastair places focus on sound development and architectural practices that will help you become a better developer, capable of designing high-performance, robust, maintainable database applications. He shows you how to apply notable features in SQL Server such as encryption and support for hierarchical data. If developing for SQL Server is what puts the bread on your table, you can do no better than to read this book and to assimilate the expert-level practices that it provides. Promotes expert-level practices Leads to high performance, scalable code Improves productivity, getting you home in time for dinner.